Using drug chemical structures in the education of pharmacology and clinical therapeutics key concepts - Abu Deiab, Ghina'a I (2023)
Medicinal chemistry made it possible for pharmacists to propose pharmacodynamics and pharmacokinetics explanations of many existing drugs. Moreover, medicinal chemistry education provides pharmacy students with a reasonable understanding of drug physicochemical properties, mechanism of action (MOA), side effects, metabolism and structure-activity relationship (SAR). This paper highlights the importance of these medicinal chemistry key elements in understanding other pharmacy core courses, mainly pharmacology and clinical therapeutics. Such elements can be utilized as a tool for pharmacists while training or counseling their patients on the use of their treatments. Different new examples from the literature have been incorporated in this paper to show how chemical structures of existing drugs can provide essential information about main concepts in the education of pharmacology and clinical therapeutics, and the key structural elements for the discovery and development of other same class drugs.